Protein Profiles of Individuals with Erosive Tooth Wear - Aida Mulic; Anne Bjorg Tveit; Nicholas Modesto Vieira; Kirsten Limesand; Alexandre Rezende Vieira (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine if protein profiles identified in saliva could be used to determine risk and severity of erosive tooth wear. Material and Methods: Three types of saliva sampling were performed to obtain saliva from 34 18-year old individuals that received regular dental check-ups, along with clinical status of the dentition and risk factor related to erosive tooth wear using the VEDE scale. Protein profiles in saliva were determined using electrophoresis and the calculation of the percentage of a specific band at a specific molecular weight in relationship to the total protein in that sample (% of total) using molecular weight standards. This quantification was repeated for each protein band across a range of molecular weights for each sample to test for association with erosive tooth wear status. Results: There were no differences in the number of detectable proteins sourced from the parotid gland, nor the unstimulated and stimulated whole saliva. Five out of the 34 individuals had no signs of erosive tooth wear despite an acidic diet and were more likely to have proteins with molecular weight smaller than 1 KDa (p=0.03). Conclusion: There is potential for the use of protein profiling to determine risks for erosive tooth wear.